2014
DOI: 10.3892/or.2014.3358
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of galectin-1 suppresses the growth and invasion of osteosarcoma cells through inhibition of the MAPK/ERK pathway

Abstract: Abstract. Galectin-1 (GAL1), a widely expressed β-galactoside-binding protein, exerts pleiotropic biological functions. GAL1 has been found to be upregulated in many malignancies; yet the role of GAL1 in the pathophysiology of human osteosarcoma (OS) remains uncertain. The present study was carried out to investigate the expression of GAL1 in human OS tissues and to explore its effects on the growth and invasion of OS cells. OS and corresponding adjacent non-cancerous tissues (ANCT) were collected from 30 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…5A, downregulation of galectin-3 markedly inhibited the activity of MEK/ERK signaling (P<0.01), suggesting that the MEK/ERK signaling pathway may act as a downstream effector of the malignant properties of MG63 cells. As the MEK/ERK signaling pathway has been demonstrated to be involved in the regulation of OS-cell invasion (11,12), the present study used curcumin, an agonist of MEK, to upregulate the activity of the MEK/ERK signaling pathway. As shown in Fig.…”
Section: Knockdown Of Galectin-3 Suppresses Migration and Invasion Ofmentioning
confidence: 99%
“…5A, downregulation of galectin-3 markedly inhibited the activity of MEK/ERK signaling (P<0.01), suggesting that the MEK/ERK signaling pathway may act as a downstream effector of the malignant properties of MG63 cells. As the MEK/ERK signaling pathway has been demonstrated to be involved in the regulation of OS-cell invasion (11,12), the present study used curcumin, an agonist of MEK, to upregulate the activity of the MEK/ERK signaling pathway. As shown in Fig.…”
Section: Knockdown Of Galectin-3 Suppresses Migration and Invasion Ofmentioning
confidence: 99%
“…Of note, we identified 10 hub IRGs, namely CXCR3, CXCR4, CCR5, CCL5, CXCL10, CXCL12, CXCL16, OPRL1, S1PR1, and GAL. Among them, CXCR3 28 , CXCR4 29 , CCR5 30 , CCL5 31 , CXCL16 32 , CXCL10 33 , CXCL12 34 and GAL 35 have been widely studied in OS, and are involved in the occurrence, metastasis, and angiogenesis of OS. OPRL1 encodes proteins that are endogenous opioid-related neuropeptides and nociceptin/orphanin receptors, which plays a key role in pain perception and nociception 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barrionuevo and colleagues showed that soluble galectin-1 stimulated ERK-1/2 phosphorylation in human monocytes, and that inhibiting the upstream kinase MEK could reverse the effects of galectin-1 on macrophage major histocompatibility complex II and fragment crystallizable gamma receptor I expression 10 . Galectin-1 stimulation has further been shown to activate ERK in airway epithelium 44 and correlates with ERK activity in allergic conjunctivitis 45 , osteosarcoma growth 46 , and lung cancer progression 47 .…”
Section: Discussionmentioning
confidence: 99%
“…in allergic conjunctivitis 45 , osteosarcoma growth, 46 and lung cancer progression. 47 This ERK-mediated signaling is distinct from the myeloid differentiation primary response gene 88-dependent signaling we have noted on PDO fibers.…”
Section: Discussionmentioning
confidence: 99%